Inequalities creating economic barriers to owning mobile phones in India: Factors responsible for the gender digital divide. (November 2016) - Potnis, Devendra
In India, men own around 70% of mobile phones, creating a gender digital divide for the most widely owned information and communication technology (ICT) in the world. This study investigates the factors responsible for the inability of 245 female slum-dwellers in India earning less than 2 a day to own a mobile phone. Open, axial and selective coding of survey responses shows that socio-cultural, economic, demographic, psychological, communication-related, and health related inequalities in the lives of the respondents create eight economic barriers precluding respondents from owning some of the least expensive mobile phones worth 15 or so on installments of 1 a month.